Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Pharmacological postconditioning by bolus injection of phosphodiesterase-5 inhibitors vardenafil and sildenafil - Bernd Ebner; Annette Ebner; Anna Reetz; Stefanie Böhme; Antje Schauer; Ruth H. Strasser; Christof Weinbrenner (Molecular and Cellular Biochemistry, 2013)

Uncoupled eNOS annihilates neuregulin-1β-induced cardioprotection: a novel mechanism in pharmacological postconditioning in myocardial infarction - Bernd Ebner; Stefan A. Lange; Thomas Eckert; Clementine Wischniowski; Annette Ebner; Rüdiger C. Braun-Dullaeus; Christof Weinbrenner; Carsten Wunderlich; Gregor Simonis; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2013)

Inhibition of anti-apoptotic signals by Wortmannin induces apoptosis in the remote myocardium after LAD ligation: evidence for a protein kinase C-δ-dependent pathway - Stephan Wiedemann; Teresa Wessela; Kerstin Schwarz; Dirk Joachim; Marcel Jercke; Ruth H. Strasser; Bernd Ebner; Gregor Simonis (Molecular and Cellular Biochemistry, 2013)

Ischemic post-conditioning reduces infarct size of the in vivo rat heart: role of PI3-K, mTOR, GSK-3β, and apoptosis - Claudia Wagner; Diana Tillack; Gregor Simonis; Ruth H. Strasser; Christof Weinbrenner (Molecular and Cellular Biochemistry, 2010)

Stimulation of adenosine A2b receptors blocks apoptosis in the non-infarcted myocardium even when administered after the onset of infarction - Gregor Simonis; Stephan Wiedemann; Dirk Joachim; Christof Weinbrenner; Rainer Marquetant; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2009)

Chelerythrine treatment influences the balance of pro- and anti-apoptotic signaling pathways in the remote myocardium after infarction - Gregor Simonis; Stephan Wiedemann; Kerstin Schwarz; Torsten Christ; Daniel G. Sedding; Xinjian Yu; Rainer Marquetant; Ruediger C. Braun-Dullaeus; Ursula Ravens; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2008)

Protein kinase C in the human heart: differential regulation of the isoforms in aortic stenosis or dilated cardiomyopathy - Gregor Simonis; Steffen K. Briem; Steffen P. Schoen; Manja Bock; Rainer Marquetant; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2007)

Dual mechanism of autoregulation of protein kinase C in myocardial ischemia - Gregor Simonis; Steffen P. Schoen; Martin U. Braun; Stefan Lichte; Rainer Marquetant; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2007)

Apoptosis at a distance: Remote activation of caspase-3 occurs early after myocardial infarction - Kerstin Schwarz; Gregor Simonis; Xinjian Yu; Stephan Wiedemann; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2006)

Regulation of protein kinase C isozymes in volume overload cardiac hypertrophy - Martin U. Braun; Paul LaRosée; Gregor Simonis; Mathias M. Borst; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2004)